Assessment and design considerations for single layer cylindrical lattice shells subjected to seismic loading. (June 2021) - Cedrón, F.; Elghazouli, A.Y.
Abstract: This paper examines the main considerations related to the seismic design and assessment of single layer steel cylindrical lattice shells, and offers recommendations for their practical application. Geometric configurations covering a wide range of rise to span ratios are considered within the investigation. An insight into the relative influence of seismic loading on shell design, in comparison to gravity conditions, is firstly provided through the use of digital parametric engineering procedures. This is followed by linear elastic response assessments which are used to propose a simplified procedure for estimating the internal seismic forces for the purpose of member sizing in early design stages. Suitable approaches for pushover analysis are then discussed and used to identify inherent plastic mechanisms. The results of incremental nonlinear dynamic analysis, using a suite of fourteen records, are also employed in order to validate the findings and to further assess the ultimate response under realistic seismic loading conditions. Based on the findings, representative ranges for behaviour factors and displacement modification coefficients are derived alongside discussions on their implementation within codified seismic design procedures. Apart from providing recommendations for simplified design approaches, the assessments presented in this paper can also be used to support detailed performance based guidelines as well as for informing geometry and size optimisation strategies.